Milwaukee Shoulder-Knee Syndrome: A Case Report - Berrin Leblebici,; Kübra Ustaömer,; Nuri Çetin,; Aysun Uğuz, (Archives of Rheumatology, 2008)
Basic calsium phospate crystals frequently may form asymptomatic deposits that may give rise to several clinical syndromes, including calsific periarthritis, tendinitis, bursitis, Milwaukee shoulder syndrome, osteoarthritis, calcific tendinitis and bursitis, and mixed crystal deposition in and around joints. Milwaukee shoulder syndrome is a well defined clinical entity that can be observed particular in older women. It is a destructive arthropathy associated with the deposition of cristals, rotator cuff tear, and joint instability. Clinical features include pain, swelling and progressive functional impairment. (Rheumatism 2008 23: 66-8)